Biology, bionomics and life-table studies of Anopheles stephensi (Diptera: Culicidae) in Sri Lanka and estimating the vectorial potential using mathematical approximations. (April 2023) - Jude, Justin; Gunathilaka, Nayana; Udayanaga, Lahiru; Fernando, Deepika; Premarathne, Prasad; Wickremasinghe, Rajitha; Abeyewickreme, Wimaladharma
Abstract: Background: Anopheles stephensi is an invasive mosquito in Sri Lanka that can potentially transmit malaria. The transmission intensity is linked with biology, bionomic and behavioral aspects of a vector that are associated with the Vectorial Capacity (VC). However, the influence of larval conditions eventually affects the vectorial potential of An. stephensi are not well understood. Methods: A colony of An. stephensi was established at the Regional Centre of the Open University of Sri Lanka, Jaffna District. The colony was maintained under confined conditions according to standard protocols. Biotypes of An. stephensi were characterized by referring to the number of egg ridges. Information on (a) biological aspects of eggs (duration for egg hatching, egg development and hatchability), (b) larval development time, larval survivorship pupation success, resting depth of larvae), (c) pupae (adult emergence rate, average time for adult emergence) and (d) adults (biting frequency, mating success gonotrophic cycle, fecundity, duration for egg-laying, percentage of sexes, adult survival/longevity) were evaluated under life-table analysis. Further, selected morphometric characters of each life cycle stage were recorded from the eggs (length and breadth), larvae (head length, width of head, length of thorax, width of thorax, length of abdomen, width of abdomen, and the total length of larvae), pupae (cephalothoracic length and width) and adults (length & width of wing, thorax and abdomen). The VC was calculated using a mathematical-based approach. Descriptive statistics, General Linear Model (GLM) and independent-sample t -test were used for the statistical analysis. Results: All three biotypes were identified based on egg morphology. Mysorensis biotype (47%; n  = 470) was predominant followed by type (38.1%; n  = 381) and intermediate (14.9%; n  = 149). The mean egg length ( F (2, 997)  = 3.56; P  = 0.029) and breadth ( F (2, 997)  = 4.57; P  = 0.011) denoted significant differences among the three biotypes. The mating success of females observed was 80.7 ± 4.45%. The mean hatching period was 1.9 ± 0.03 days, with a hatching rate of 86.2 ± 0.77%. Overall, 8.0 ± 0.14 days were required for larval development and 30.3 ± 0.14 h were spent in the pupal stage. The pupation success was 94.5 ± 0.37%, and the majority were males (53.1 ± 0.73%). The mean fecundity was 106.5 ± 6.38 eggs and a gonotrophic cycle of 3.4 ± 0.06 days. The female survival rate was 43.2 ± 2.4%, with a mean biting frequency of 66.6 ± 3.5%. The average VC of adult An. stephensi was estimated to be 18.7. Conclusions: The type biotype, which is an effective vector in the Indian subcontinent is present in Sri Lanka. According to the mathematical approximation, An. stephensi found locally has a vectorial capacity of over 18. Therefore, this study warrants the health authorities and vector control programmes to continue the entomological surveys, monitoring of vector densities and implementing appropriate vector control interventions based on biology and bionomic information of vectors. Highlights: Anopheles stephensi is an invaded vector in Sri Lanka. However, the vectorial potential of this mosquito is still unknown. The life-table aspects of vectors are useful tools in predicting the transmission potential, forecasting disease outbreaks and designing appropriate vector control interventions. The present study documents the first descriptive study on the life-table, biology and bionomic aspects of locally reported An. stephensi and estimates the vectorial potential using mathematical approximations. The data herein emphasize the necessity of implementing appropriate vector control interventions based on the biology and bionomic information of disease vectors.